Surgical management of duodenal web in an adult presenting with melaena; Case report and literature review. (November 2021) - Grinlinton, Megan; Welsh, Fraser; Phillips, Liz; Chang, Wai Keat
Abstract: Introduction: Duodenal web is a rare pathology presenting infrequently in adults. Diagnosis is challenging and definitive management is commonly delayed. We present a case of a patient with a late diagnosis of duodenal web, who underwent laparotomy, intraoperative gastroscopy and surgical removal of the web performed by two general surgeons. Case presentation: A 32-year-old woman with a previous diagnosis of irritable bowel syndrome presented with a three day history of abdominal pain, nausea and anorexia, and a one day history of melaena and haematemesis. Investigations including a magnetic resonance enterography, barium swallow study and gastroscopy revealed the diagnosis. The patient underwent laparotomy and excision of duodenal web. Intraoperative gastroscopy assisted with identification of the web's anatomical location. A longitudinal duodenotomy was performed and this was closed in a transverse fashion using the Heineke-Mikulicz technique. Discussion: This case reports successful application of intraoperative gastroscopy during laparotomy and duodenotomy. Longitudinal duodenotomy with excision of the web and transverse closure of the duodenum appears to be the best approach. There are no previous publications detailing gastroscopy at the time of laparotomy with duodenal web. This technique may be utilised in appropriate situations to improve operative accuracy. Conclusion: Duodenal web is a rare entity in adults, and delayed diagnosis may lead to significant patient morbidity. Incorporating intraoperative endoscopy ensures accurate anatomical visualisation. This technique avoids duodenectomy, organ damage, bypass, or an unnecessarily large incision. Highlights: Duodenal web is a rare diagnostic dilemma found infrequently in adults. Duodenal web is frequently misdiagnosed and may not be visible on gastroscopy. Investigations such as magnetic resonance enterography and barium swallow studies may be useful adjuncts for diagnosis. Surgical management via laparotomy and duodenotomy are the best agreed cure for duodenal web. Intraoperative gastroscopy is a novel technique that may improve patient outcomes by enhancing anatomical accuracy.